PENGUATAN KEMANDIRIAN DAN KREATIVITAS SISWA MELALUI IMPLEMENTASI PENDIDIKAN KEWIRAUSAHAAN DALAM PROGRAM P5RA DI MTSN 9 JEMBER - Utami, Yudy Tri; Ulum, Darul; Mukhlis, Akhmad (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
The implementation of entrepreneurship education in Indonesia contributes significantly to fostering students' independence and creativity, while equipping them with life skills that are in line with the needs of the world of work and social change. This service research aims to explore and analyse the application of entrepreneurship education in the context of the Pancasila and Rahmatan Lil Alamin (P5RA) Student Profile Strengthening Project and its impact on students' creativity, independence, and character building. This research method uses a descriptive qualitative approach. This research involved students in grades VII and VIII of MTs Negeri 9 Jember as subjects. Data were collected through observation, interviews, questionnaires, and documentation, and analysed descriptively. The results of this service research show that the integration of entrepreneurship with the values of Pancasila and Rahmatan Lil Alamin can increase student creativity in designing and implementing entrepreneurial projects based on social needs. In addition, this programme also succeeded in increasing students' independence in making decisions and managing entrepreneurial projects. However, there are challenges related to limited facilities and time management that still need to be considered to improve the effectiveness of the implementation of this programme. Therefore, it is necessary to co-operate with the role of teachers, parents and skills assistants so that overall, entrepreneurship education in the P5RA Project carried out makes a positive contribution to the improvement and development of students' skills